Silobran - Šepec, Miha (Podjetje in delo, 2020)
Self-defence is considered to be the oldest, most traditional and most classic reason for excluding the illegality of an individual's act, which otherwise fulfils the essence of a crime. At its core, this institute means that no one is obliged to subject himself to an unlawful attack and that everyone has the right to defend themselves against such an attack. But despite the traditional stability of this criminal law construct, it is anything but simple and theoretically finalized. Namely, many dogmatic dilemmas arise within the self-defence, which can also be a hard nut to crack for our case law. In this paper, I address two contemporary self-defence dilemmas. Namely, the question of goods that can be protected with self-defence, and whether self-defence can be used to take the life of another person in the interest of protecting property.